2013
DOI: 10.1136/annrheumdis-2013-eular.2897
|View full text |Cite
|
Sign up to set email alerts
|

AB0575 Prevalence of hla-cw * 06 and * 07 and its relationship with psoriatic arthritis in northwestern spain.

Abstract: Background Psoriatic arthritis (PsA) is a disease developed in 10-20% of psoriasis patients. HLA–Cw*06 has been identified as the major genetic determinant of susceptibility to psoriasis. Objectives To estimate the prevalence of HLA-Cw6 and Cw7 in healthy population, patients with psoriasis without joint disease and patients with PsA and to analyze the influence of both alleles in the characteristics of PsA. Methods Genotyping of HLA-Cw * 06 and * 07 was performed on DNA samples of 390 Caucasian subjects by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There were fewer reports regarding the association of HLA-Cw*07 and psoriatic disease. There were reports to show no association between HLA-Cw*07 and psoriatic disease, and PsA cases were less likely to be carriers of the HLA-Cw*07[47, 48]. In one Spanish study, HLA-Cw*0701 was found under-represented in PsA patients compared to controls and there was a positive association between psoriatic spondylitis and HLA-Cw*0702[11].…”
Section: Discussionmentioning
confidence: 99%
“…There were fewer reports regarding the association of HLA-Cw*07 and psoriatic disease. There were reports to show no association between HLA-Cw*07 and psoriatic disease, and PsA cases were less likely to be carriers of the HLA-Cw*07[47, 48]. In one Spanish study, HLA-Cw*0701 was found under-represented in PsA patients compared to controls and there was a positive association between psoriatic spondylitis and HLA-Cw*0702[11].…”
Section: Discussionmentioning
confidence: 99%